The eurosystem money market auctions: a banking perspective - Nikolaus Bartzsch; Ben R. Craig; Falko Fecht (Deutsche Bundesbank, 2005)
This paper analyzes the individual bidding behaviour of German banks in the money market auctions conducted by the ECB from the beginning of the third quarter of 2000 to the end of the first quarter of 2001. Our approach takes a variety of characteristics of the individual banks into account. In particular, we consider variable that capture the different use of liquidity and the different attitude towards liquidity risk of the individual banks. It turns out that these characteristics are reflected in the banks' respective bidding behaviour to a large extent. Thus our study contributes to a deeper understanding of the way liquidity risk is managed in the banking sctor.
Keywords: G21; E51; 330; Money Market Auctions; Liquidity Management; Interbank Market; Geldmarkt; Auktion; Bank; Bankenliquidität; EU-Staaten